The Impact of Enterprise Digital Intelligence Transformation on Cash Holdings: Theoretical Mechanisms and Empirical Evidence from China - Lv, Mingxuan (Asia Pacific Economic and Management Review, 2025)
In the context of the sweeping global digital economy, the deep integration of digital technologies—such as big data, artificial intelligence, cloud computing, and blockchain—with the real economy has become a critical engine for high-quality enterprise development. While existing literature has extensively discussed the impact of digital transformation on total factor productivity and innovation output, its influence on corporate financial policies, particularly cash holding decisions, remains under-explored. This paper empirically investigates the impact of enterprise digital intelligence transformation on corporate cash holdings using a comprehensive dataset of A-share listed companies on the Shanghai and Shenzhen Stock Exchanges from 2013 to 2022. The study constructs a robust index of digital transformation through textual analysis of annual reports. The empirical results demonstrate that digital intelligence transformation has a significant and robust negative impact on the level of corporate cash holdings. Theoretical analysis reveals that digitalization optimizes cash management through three distinct channels: (1) The "Information Effect," where improved forecasting capabilities reduce the precautionary demand for cash; (2) The "Governance Effect," where enhanced transparency and internal controls curb agency costs and the hoarding of free cash flow; and (3) The "Supply Chain Effect," where digital supply chain finance accelerates working capital turnover. Furthermore, heterogeneity analysis indicates that this inhibitory effect is more pronounced in non-state-owned enterprises, firms with lower analyst coverage, and companies located in regions with weaker marketization. This research not only enriches the theoretical framework regarding the economic consequences of digital transformation but also provides critical empirical evidence for corporate liquidity management strategies in the digital era.